Matrilineal Marriage Tradition: A Study of the Customary Law of “Women Buying Men” in Padang Pariaman - Fadilah, Kurniawan Agung (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2025)
Bajapuik is one of the traditions of women buying men, the marriage practice of the Minangkabau people who adhere to the matrilineal kinship system, especially in the Padang Pariaman area. Women’s traditions have a dominant role, in the economic aspect and the determination of the social status of the family. This study aims to examine the existence of customary law that governs these practices, as well as how local cultural values are maintained amid the influence of modernity. Through a descriptive qualitative method approach by interviewing directly from relevant sources who have implemented the custom, this study found that the practice is still carried out with certain adaptations, and has implications for social relationships, inheritance rights, and family structure. The results of this study show that the law of adat in Padang Pariaman is dynamic and able to adapt without abandoning the core values of matrilineal culture.